Internet applications - Zeki, Akram M. (IIUM Press, 2015)
Internet application is becoming part and parcel of every human activity in the twenty first century. With today’s advancement of technology, Internet remains an integral part of life; almost entire human activities today rely on Internet. Internet application is becoming the fastest growing sector of human activities. The Internet hold a global system of everything, where interconnected networks of computing devices interact with each other under certain standard protocol refers to as Internet protocol suite normally called Transmission control protocol /Internet protocol (TCP/IP) to serve several connecting devices. This book aims at providing the basis and fundamentals of The Internet, Internet use and Internet application. The Internet carries an extensive range of information resources and services, such as the inter-linked hypertext documents of the World Wide Web (WWW), the infrastructure to support email, and peer-to-peer networks. This book expose almost all the necessary procedure used in implementation and application of the Internet resources. The book provides an introductory detail to Computer Network for Internet application which covers variety of topics relating to the issues and challenges. Readers of this book are expected to gain an in-depth knowledge on the basics of the Internet and World Wide Web (WWW). The book also exposes the standard of Internet Protocol suites. And other protocols like Messaging protocols and standard in the Internet, Wimax and Wi-Fi technologies standards and trend. Although the book dwells on internet application, but areas like multimedia in developing Islamic website are provided in the book, other area of multimedia security in the Internet and general application of Multimedia to Internet are provided as well. This is because of the important of multimedia to the Internet development. Hence an application of Multimedia e-lecture note, E-books Islamic presentation and web design are provided. The reader of this book is expected to be expose to the fundamental of computer wired/wireless networks, the characteristics of different classification of computer network and an understanding of the fundamentals of computer of Internet application in today’s world.